2015
DOI: 10.3177/jnsv.61.161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Beta-Alanine Supplementation on Anaerobic Performance in Trained Female Cyclists

Abstract: Summary Longitudinal beta-alanine (BA) supplementation can improve exercise performance in males through increases in carnosine; however, females experience greater relative increases in carnosine compared to males. This potentially allows females to benefit from acute BA doses; however, effects of an acute BA dose on performance in females remain unknown. The purpose of this investigation was to evaluate how an acute dose of 1.6 g BA affects anaerobic performance in female cyclists. Twelve females (age526.661… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…However, this is the first study to demonstrate that only the combination of BA plus plyometric training induced a greater ( p < 0.05) increase in 20 m multistage shuttle run test times compared to the CONTROL group (Table 3). The ergogenic effects of beta-alanine on endurance exercise performance, especially in open-ended exercise tasks (Hobson et al, 2012) until volitional fatigue (Trexler et al, 2015), such as in this study, could occur through increased oxygen utilization and work production in later stages of the test (Smith et al, 2009), an increased ventilatory threshold (Stout et al, 2007) or a reduced rating of perceived exertion (Glenn et al, 2015b). …”
Section: Discussionmentioning
confidence: 90%
“…However, this is the first study to demonstrate that only the combination of BA plus plyometric training induced a greater ( p < 0.05) increase in 20 m multistage shuttle run test times compared to the CONTROL group (Table 3). The ergogenic effects of beta-alanine on endurance exercise performance, especially in open-ended exercise tasks (Hobson et al, 2012) until volitional fatigue (Trexler et al, 2015), such as in this study, could occur through increased oxygen utilization and work production in later stages of the test (Smith et al, 2009), an increased ventilatory threshold (Stout et al, 2007) or a reduced rating of perceived exertion (Glenn et al, 2015b). …”
Section: Discussionmentioning
confidence: 90%
“…Over long time periods, it is believed that it can increase the effect of international road cyclist training of anaerobic and aerobic high effect time 1-day micro cycle anaerobic threshold but long-term efficiency as 4-to-8-week same periodization because estimated to power and lactate mmol increase [5,20,24,25,26,27,28,29]. Male cyclist at least per week 7 hours training about 20 km trial load is occur 7/Watt power increase sequence of intervals but increasing mechanism in the muscle would not proper training into beta-alanine use because 48 hours or 24 hours eliminated lactate as well as recovery most speed.…”
Section: Discussionmentioning
confidence: 99%
“…Same participation groups regardless of experience characteristics aerobic power has been limited long time periods. Anaerobic power reported that, time as periods to measurement protocols are values parameter obtainement eligibility power output reference [25,26]. Therefore, races cycling time-period anaerobic less were founded [5].…”
Section: Methodsmentioning
confidence: 99%
“…In humans, muscle carnosine content ranges from 17.5 6 4.8 mmol$kg -1 dm in women to 21.3 6 4.2 mmol$kg 21 dm in men (81). Literature is consistent to show the efficacy of b-alanine supplementation on the increase of muscle carnosine content (10,34,35,51,56) within as little as 2 weeks (105); however, acute doses have proven ineffective (46). After longitudinal supplementation, carnosine levels are documented to increase up to 65% (51) and 80% (56) after 4 and 10 weeks, respectively.…”
Section: Beta-alaninementioning
confidence: 99%